Internet Screen Time and Related Factors: Threat to Adolescence in Indonesia - Kurniasanti, Kristiana; Firdaus, Karina; Christian, Hans; Wiguna, Tjhin; Wiwie, Martina; Ismail, Raden (Makara Human Behavior Studies in Asia, 2019)
The widespread use of the internet has produced both positive and negative impacts. Among the latter is internet addiction (IA). The worldwide prevalence of this addiction has been measured at approximately 6%, although the specific prevalence in Indonesia is uncertain because no validated instrument to measure IA has been developed for the Indonesian context. Hence, screen time was used in this study as an alternative measure of the magnitude of IA in Indonesia, where more than 6 hours is considered risk for IA. Researchers measured internet screen time (IST) and potential related factors in adolescents. The subjects of this cross-sectional study were 200 junior and senior high school students in Jakarta, Indonesia, who completed a questionnaire assessing IST and related factors. IST duration was divided into two categories: short (<6 hours/day) and long (>6 hours/day). Out of 200 students, 68 (34%) had long ISTs, with related factors being senior high education, positive perception of IA, and excessive body mass index. The percentage of students with long ISTs was quite high. A valid and reliable diagnostic tool for IA is a necessity. Prompt prevention is necessary to prevent adolescent IA, especially in higher-risk adolescents.